Descending nociceptive inhibition is modulated in a time-dependent manner in a double-hit model of chronic/tonic pain. (19th February 2016) - Parent, A.J.; Tétreault, P.; Roux, M.; Belleville, K.; Longpré, J.-M.; Beaudet, N.; Goffaux, P.; Sarret, P.
Highlights: Time-dependent decrease in nociceptive response to formalin observed in CCI rats. Peak hypoalgesic response to formalin observed at day 28 in CCI rats. Hypoalgesic response to formalin subsided progressively after day 28 in CCI rats. Early increase in basal CSF 5-HT/NE levels in CCI rats and return to baseline at day 28. Abstract: Clinical evidences suggest that an imbalance between descending inhibition and facilitation drives the development of chronic pain. However, potential mechanisms promoting the establishment of a persistent pain state and the increased pain vulnerability remain unknown. This preclinical study was designed to evaluate temporal changes in descending pain modulation at specific experimental endpoints (12, 28, 90 and 168 days) using a novel double-hit model of chronic/tonic pain (first hit: chronic constriction injury (CCI) model; second hit: tonic formalin pain in the contralateral hindpaw). Basal activity of bulbo-spinal monoaminergic systems was further assessed through liquid chromatography coupled with tandem mass spectrometry (LC–MS/MS) screening of cerebrospinal fluid (CSF). We found that CCI-operated rats exhibited a reduced nociceptive response profile, peaking on day 28, when subjected to tonic pain. This behavioral response was accompanied by a rapid increase in basal CSF serotonin and norepinephrine levels 12 days after neuropathy, followed by a return to sham levels on day 28. These molecular and behavioral adaptive changes in descending pain inhibition seemed to slowly fade over time. We therefore suggest that chronic neuropathic pain produces a transient hyperactivation of bulbo-spinal monoaminergic drive when previously primed using a tonic pain paradigm (i.e., formalin test), translating into inhibition of subsequent nociceptive behaviors. Altogether, we propose that early hyperactivation of descending pain inhibitory mechanisms, and its potential ensuing exhaustion, could be part of the temporal neurophysiological chain of events favoring chronic neuropathic pain establishment.